Preparation method of lithium-based ceramic granulated powder, lithium-based ceramic granulated powder and lithium-based ceramic material
By using organic solvents and water as composite solvents, spray granulation of lithium-based ceramic prefixed powder is solved, and the problem of difficult to take into account both the fluidity and fillability of the granulated powder in the prior art is realized, and high-density lithium-based ceramic green body and sintered high-density material are realized.
Patent Information
- Application Number
- CN202411680686.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-11
AI Technical Summary
The existing lithium-based ceramic granulation process is difficult to meet the fluidity and fillability requirements of the granulated powder at the same time, resulting in a small green density during the pressing and molding process, affecting the density of the ceramic after sintering.
By using organic solvents and water as composite solvents, the lithium-based ceramic prefixed powder is dispersed and arranged into a slurry, and the granulated powder is obtained after spray drying, which not only reduces the hardness of the granulated powder, improves its fillability, but also maintains good spherical shape and fluidity.
The good fluidity and fillability of lithium-based ceramic granulated powder are achieved, and can be used to press and obtain green body with higher density, so that the density of lithium-based ceramic material is obtained after sintering, which improves the performance of the material.
Smart Images

Figure CN119591401A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium-based ceramic production, and specifically relates to a preparation method of lithium-based ceramic granulation powder, lithium-based ceramic granulation powder and lithium-based ceramic material. Background Art
[0002] Lithium-based ceramics represented by garnet-type (LLZO) solid electrolytes have high ionic conductivity and are stable to lithium metal. They are one of the most popular solid electrolyte materials at present. They can be used in all-solid-state batteries and lithium extraction, and have great application prospects.
[0003] In the process of ceramic production, molding is a key step. The so-called molding is to convert various dispersed raw materials of ceramics into blocks. There are many mature molding processes at present, the more common ones are dry pressing, cold isostatic pressing, slip casting, tape casting, extrusion molding, injection molding and other processes. Among them, dry pressing and cold isostatic pressing can be collectively referred to as compression molding. For ceramic bodies with regular shapes such as plates or tubes, compression molding has the advantages of simple process, low production cost, continuous and large-scale production, etc., and has been widely used in industrial production. In order to meet the requirements of compression molding for powder fluidity and filling properties, the powder needs to be granulated before molding to form granulated powder with good fluidity and filling properties.
[0004] The existing granulation process often cannot meet the requirements of granulation powder fluidity and filling properties at the same time. Summary of the invention
[0005] In view of this, the present application provides a lithium-based ceramic granulation powder and a preparation method and application thereof, aiming to provide a lithium-based ceramic granulation powder with good fluidity and filling properties by controlling the hardness and sphericity of the granulation powder.
[0006] In a first aspect, the present application provides a method for preparing lithium-based ceramic granulated powder, comprising the following steps:
[0007] Step S1: providing raw materials according to the stoichiometric ratio of lithium-based ceramics, and pre-sintering to obtain lithium-based ceramic pre-sintered powder, wherein the raw materials include a lithium source;
[0008] Step S2: mixing the lithium-based ceramic pre-sintered powder with a composite solvent to prepare a slurry, wherein the composite solvent includes an organic solvent and water;
[0009] Step S3: subjecting the slurry to a spray granulation treatment to remove the composite solvent and obtain lithium-based ceramic granulated powder.
[0010] Based on the present application, the inventors found that since the raw materials for preparing lithium-based ceramics include a lithium source, and the lithium source (such as lithium carbonate Li2CO3) is easily ionized and / or hydrolyzed in water, the pH value of the formed slurry is relatively high. Although a granulated powder with good sphericity and good fluidity can be obtained after spray drying, the hardness of the granulated powder is relatively high. In the subsequent pressing and molding process, since it is not easy to break and has poor filling properties, the density of the green body obtained by pressing is relatively low, which affects the density of the ceramic after sintering. The present application uses an organic solvent and water as a composite solvent to disperse the lithium-based ceramic pre-fired powder into a slurry, which can effectively reduce the pH of the slurry, and the hardness of the granulated powder obtained after spray drying is relatively high. The granulation powder obtained has good filling properties. At the same time, the inventors also found that if an organic solvent is used alone to configure the pre-fired powder to form a slurry, the granulated powder obtained by spray drying has a low hardness and good filling properties, but is not easy to form a sphere, resulting in poor fluidity. Therefore, it is not easy to be pressed into a high-density lithium-based ceramic green body. At the same time, pure organic solvent as a solvent will also affect the safety of spray drying. Therefore, the present application uses an organic solvent and water as a composite solvent to obtain a granulated powder with low hardness and good sphericity. It has good fluidity and filling properties during the molding process and can be used to press a green body with a higher density, thereby obtaining a lithium-based ceramic material with a higher density.
[0011] In some embodiments, in step S2, the organic solvent includes at least one of ethanol, propanol, and n-butanol. It is understood that the organic solvent includes but is not limited to the above-mentioned ones, and those skilled in the art can select organic solvents miscible with water known in the art according to the teachings of this application according to actual needs. Preferably, the organic solvent is ethanol. Ethanol has good mutual solubility with water, and is not easy to remain after spray drying, thereby reducing the introduction of impurities in the ceramic.
[0012] In some embodiments, in the step S2, in the composite solvent, the mass ratio of the organic solvent to water is 1:2 to 5. Based on the above embodiment, when the mass ratio of the organic solvent to water meets the above conditions, the obtained granulated powder can better balance hardness and sphericity, has better fluidity and filling properties, and can be used to prepare high-density lithium-based ceramic green bodies. For example, the mass ratio of the organic solvent to water can be 1:2, 1:2.2, 1:2.5, 1:2.8, 1:3, 1:3.2, 1:3.5, 1:3.7, 1:4, 1:4.3, 1:4.5, 1:4.8, 1:5, or within the range of any of the above values. Preferably, the mass ratio of the organic solvent to water is 1:2.5 to 3.
[0013] In some embodiments, in step S2, the solid content of the slurry is 20wt% to 70wt%. Based on the above embodiment, when the solid content of the slurry meets the above conditions, the granulated powder obtained has better sphericity and particle size, better fluidity and filling properties, and can be used to prepare high-density lithium-based ceramic green bodies. For example, the solid content of the slurry can be 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, or within the range of any of the above values.
[0014] In some embodiments, in step S2, the pH of the slurry is 8 to 10. Based on the above embodiment, when the pH of the slurry is within the above range, the granulated powder obtained by spray drying has a lower hardness and a higher sphericity, has better fluidity and filling properties, and can be used to prepare high-density lithium-based ceramic green bodies.
[0015] In some embodiments, in step S3, the conditions of the spray granulation treatment include: the air inlet temperature is 130-160°C. Based on the above embodiment, the evaporation rate of the composite solvent in the slurry can be controlled by controlling the air inlet temperature. When the air inlet temperature meets the above conditions, the evaporation rate inside and outside the particles is more uniform during the spray drying granulation process, and the surface tension of the granulation particles is smaller, so that a granulated powder with a smaller hardness and a higher sphericity can be obtained, which has better fluidity and filling properties. For example, the air inlet temperature can be 130°C, 132°C, 135°C, 138°C, 140°C, 145°C, 148°C, 150°C, 155°C, 160°C, or within the range of any of the above values. Preferably, the air inlet temperature is 145-155°C.
[0016] In some embodiments, in step S3, the spray granulation treatment conditions further include: introducing a gas into the air inlet, wherein the gas includes an inert gas. Based on the above embodiment, since the organic solvent in the general composite solvent is easy to burn or explode at high temperature, introducing a gas including an inert gas into the air inlet can effectively improve the safety of the spray drying process.
[0017] In some embodiments, the gas further comprises air. Based on the above embodiments, since the composite solvent is a mixture of an organic solvent and water, the threshold of combustion and explosion is relatively low, and air can also be included to reduce production costs.
[0018] In some embodiments, the volume ratio of the inert gas to air is 1:3 to 7. Based on the above embodiments, when the volume ratio of the inert gas to air meets the above conditions, it can better balance safety and economy. For example, the volume ratio of the inert gas to air can be 1:3, 1:3.2, 1:3.5, 1:3.8, 1:4, 1:4.2, 1:4.5, 1:4.8, 1:5, 1:5.5, 1:5.8, 1:6, 1:6.5, 1:7, or within the range of any of the above values. Preferably, the volume ratio of the inert gas to air is 1:4.5 to 5.5.
[0019] In some embodiments, the inert gas includes nitrogen and / or argon.
[0020] In some embodiments, the lithium-based ceramic is selected from any one of the substances shown in Formula 1;
[0021] Li 7-x LqCy 2-x M x O 12 Formula 1
[0022] Wherein, M is a doping element, and M is selected from at least one of Ta, Nb, W, and Ti; the value range of x is: 0≤x≤1.0, preferably 0.4≤x≤0.8.
[0023] Of course, the doping elements in the present application are not limited to the above-mentioned ones. Lithium-based ceramics containing other doping elements in the art, such as lithium-based solid electrolyte ceramics, are also suitable for the granulation method provided in the present application.
[0024] In some of the above embodiments, the lithium-based ceramic satisfying the above formula 1 is a LLZO-based solid electrolyte, which has high ionic conductivity, stable structure and strength, and can be used as a solid electrolyte in a battery; at the same time, by doping the M element in the Zr position, the LLZO-based solid electrolyte can maintain a cubic phase at room temperature, and the LLZO-based solid electrolyte has a higher ionic conductivity than the tetragonal phase.
[0025] In some embodiments, the raw materials further include a La source, a Zr source, and a doping element M source.
[0026] In some embodiments, the Li source includes at least one of lithium carbonate, lithium nitrate, and lithium hydroxide, preferably lithium carbonate.
[0027] In some embodiments, the La source includes at least one of lanthanum oxide, lanthanum hydroxide, and lanthanum nitrate, preferably lanthanum hydroxide.
[0028] In some embodiments, the Zr source includes at least one of zirconium oxide, zirconium hydroxide, and zirconium nitrate, preferably zirconium oxide.
[0029] In some embodiments, the doping element M source is a Ta source, and the Ta source includes one of tantalum oxide, tantalum hydroxide, and tantalum nitrate, preferably tantalum oxide.
[0030] In a second aspect, the present application provides a lithium-based ceramic granulated powder prepared according to the method described in any embodiment of the first aspect.
[0031] Based on the present application, the lithium-based ceramic granulated powder is prepared according to the method described in any embodiment of the first aspect, and therefore has the beneficial effects of the first aspect and has good fluidity and filling properties.
[0032] In a third aspect, the present application provides a lithium-based ceramic material, which is obtained by molding and sintering the lithium-based ceramic granulated powder described in any embodiment of the second aspect.
[0033] Based on the present application, the lithium-based ceramic material is obtained by molding and sintering the lithium-based ceramic granulated powder described in any embodiment of the second aspect. Since the lithium-based ceramic granulated powder has good fluidity and filling properties, a lithium-based ceramic green body with higher density can be obtained. After sintering, a lithium-based ceramic sheet with higher density can be obtained, thereby obtaining a lithium-based ceramic material with fewer defects and good performance.
[0034] In some embodiments, the molding comprises: pressing the lithium-based ceramic granulation powder under a pressure of 180 to 220 MPa to obtain a lithium-based ceramic green body, wherein the density of the lithium-based ceramic green body is 2.6 to 2.80 g / cm 3 Based on the above embodiment, the density of the lithium-based ceramic green body can be 2.6-2.80 g / cm 3 , thereby obtaining lithium-based ceramic materials with higher density and better performance.
[0035] In a fourth aspect, the present application also provides a method for preparing a lithium-based ceramic material, comprising: forming and pressing the lithium-based ceramic granulated powder obtained by mixing, pre-firing and granulating into a lithium-based ceramic green body, and sintering the lithium-based ceramic green body to obtain a lithium-based ceramic material.
[0036] In the present application, the pre-burning process may be any suitable method in the prior art, or the following method provided in the present application:
[0037] A method for preparing lithium-based ceramic pre-sintered powder comprises the following steps:
[0038] Step S1: providing raw materials according to the stoichiometric ratio of lithium-based ceramics;
[0039] Step S2: mixing the raw materials with an alcohol solvent and grinding them to obtain a slurry;
[0040] Step S3: directly pre-sintering the slurry after drying to obtain lithium-based ceramic pre-sintered powder.
[0041] In some embodiments, in step S2, the alcohol solvent includes at least one of methanol, ethanol, and propanol;
[0042] The mass ratio of the raw material to the alcohol solvent is 0.2-0.7:1.
[0043] In some implementations, in step S2, the Dv50 of the raw materials in the slurry is below 0.5 μm.
[0044] In some embodiments, in step S3, directly pre-firing the slurry after drying it comprises: placing the slurry in a magnesium oxide crucible, drying it, and then directly pre-firing it;
[0045] Preferably, the drying conditions include: drying temperature: 70°C to 90°C; drying time: 600min to 800min.
[0046] In some implementations, in step S3, the liquid level of the slurry in the magnesium oxide crucible does not exceed 10 mm.
[0047] In some embodiments, in step S3, the conditions of the pre-calcination treatment include: heating to 390-410°C and keeping warm for 60-550 minutes, then heating to 640-660°C and keeping warm for 60-550 minutes, then heating to 710-730°C and keeping warm for 60-550 minutes, then heating to 760-770°C and keeping warm for 60-550 minutes, then heating to 910-930°C and keeping warm for 300-800 minutes;
[0048] Preferably, in step S3, the conditions for the pre-burning treatment include: heating to 390-410°C and keeping warm for 120-480 min, then heating to 640-660°C and keeping warm for 120-480 min, then heating to 710-730°C and keeping warm for 120-480 min, then heating to 760-770°C and keeping warm for 120-480 min, then heating to 910-930°C and keeping warm for 300-600 min.
[0049] In some embodiments, the heating rates in the pre-calcination treatment are independently 3 to 10° C. / min.
[0050] The lithium-based ceramic granulated powder provided by the process can be pressed and molded at any value of 180MPa, 190MPa, 200MPa, 210MPa, 220MPa or a range consisting of the above arbitrary values to obtain a lithium-based ceramic green body.
[0051] Preferably, the pressure of the compression molding is 200 MPa.
[0052] The sintering process may be any suitable method in the prior art, or the method provided in the following application:
[0053] A method for preparing a lithium-based ceramic material comprises the following steps:
[0054] Step S1: stacking a plurality of lithium-based ceramic green sheets in a thickness direction and placing them in a first crucible with a first lithium-based ceramic pre-fired powder on the bottom, wherein a second lithium-based ceramic pre-fired powder is sprinkled between the plurality of lithium-based ceramic green sheets;
[0055] Step S2: placing the second crucible upside down into the first crucible with its opening facing downward, so that the plurality of lithium-based ceramic green sheets are contained in the second crucible;
[0056] Step S3: sealing the first crucible containing the second crucible with a crucible cover and then performing a sintering process to sinter the lithium-based ceramic green body to obtain the lithium-based ceramic material.
[0057] In some embodiments, the total height h of the plurality of lithium-based ceramic green sheets stacked in the thickness direction and the height H of the second crucible satisfy: 0.3H≤h<H;
[0058] Preferably, 0.5H≤h<H;
[0059] Further preferably, 0.7H≤h<H;
[0060] Still more preferably, 0.9H≤h<H.
[0061] In some embodiments, the total height h of the plurality of lithium-based ceramic green sheets stacked in the thickness direction and the height H of the second crucible satisfy: 0.5H≤h<H; and,
[0062] When the height h1 of a lithium-based ceramic green body after a plurality of lithium-based ceramic green bodies are stacked satisfies 0.3H≤h1<0.7H, the density of the lithium-based ceramic material obtained by sintering the green body is 96% to 97%;
[0063] When the height h1 of a lithium-based ceramic green body after a number of lithium-based ceramic green bodies are stacked satisfies 0.7H≤h1<0.9H, the density of the lithium-based ceramic material obtained by sintering the green body is 97% to 99%;
[0064] When the height h1 of a lithium-based ceramic green body after a plurality of lithium-based ceramic green bodies are stacked satisfies 0.9H≤h1<H, the density of the lithium-based ceramic material obtained by sintering the green body is greater than or equal to 99%;
[0065] The height h1 is the distance between the upper surface of a lithium-based ceramic green body and the lower surface of the lowest lithium-based ceramic green body.
[0066] In some implementations, the particle size of the first lithium-based ceramic pre-fired powder is 0.5 to 5 mm; the particle size of the second lithium-based ceramic pre-fired powder is 20 to 80 μm.
[0067] In some embodiments, the step S1 further comprises: after laying a layer of second lithium-based ceramic pre-fired powder on the first lithium-based ceramic pre-fired powder, stacking a plurality of lithium-based ceramic green sheets along the thickness direction and placing them on the second lithium-based ceramic pre-fired powder.
[0068] In some implementations, the first crucible, the second crucible and the crucible cover are all made of magnesium oxide.
[0069] In some embodiments, the first lithium-based ceramic pre-fired powder and the second lithium-based ceramic pre-fired powder are independently obtained by the following methods:
[0070] Raw materials are provided according to the stoichiometric ratio of each element in the lithium-based ceramic material, wherein the raw materials include a lithium source, the mass of the lithium element in the lithium source is recorded as m, the theoretical amount of the lithium element is recorded as m0, and 1.1m0≤m≤1.2m0 is satisfied; and the raw materials are pre-fired and crushed at 800-1000°C to obtain lithium-based ceramic pre-fired powder.
[0071] In some embodiments, the lithium-based ceramic green body is obtained by the following method:
[0072] Raw materials are provided according to the stoichiometric ratio of each element in the lithium-based ceramic material, wherein the raw materials include a lithium source, the mass of the lithium element in the lithium source is recorded as m, the theoretical amount of the lithium element is recorded as m0, and 1.1m0≤m≤1.2m0 is satisfied; the raw materials are pre-fired and crushed at 800-1000°C to obtain lithium-based ceramic pre-fired powder; and the lithium-based ceramic pre-fired powder is then granulated and formed to obtain the lithium-based ceramic green body.
[0073] Compared with the prior art, the beneficial effects of the present application are at least:
[0074] (1) The granulated powder obtained by the method provided in the present application has good filling property and fluidity, and thus can be used to prepare high-density lithium-based ceramic green bodies;
[0075] (2) High-density lithium-based ceramic green bodies are easier to sinter to obtain high-density lithium-based ceramic materials, thereby improving the performance of lithium-based ceramic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1 This is a scanning electron microscope image of the granulated powder in Example 3 of the present application;
[0077] Figure 2 This is a scanning electron microscope image of the green body fracture in Example 3 of the present application;
[0078] Figure 3 This is a scanning electron microscope image of the granulated powder in Comparative Example 1 of the present application;
[0079] Figure 4 This is a scanning electron microscope image of the green body fracture in Comparative Example 1 of the present application;
[0080] Figure 5 This is a scanning electron microscope image of the granulated powder in Comparative Example 2 of the present application;
[0081] Figure 6 This is a scanning electron microscope image of the green body fracture in comparative example 2 of the present application. DETAILED DESCRIPTION
[0082] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.
[0083] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the implementation or examples are included in at least one implementation or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same implementation or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more implementations or examples in a suitable manner.
[0084] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0085] Based on the above background technology, in order to meet the requirements of powder fluidity and filling properties for compression molding, the powder needs to be granulated before molding to form granulated powder with good fluidity and filling properties. The powder obtained by spray granulation is an artificial agglomerate. The microscopic morphology of excellent granulated powder is spherical, and the particle size is distributed within a certain range, which is conducive to improving the fluidity of the powder, increasing the molding density, and reducing the sintering shrinkage. It has become the most common industrial granulation process.
[0086] After the granulation powder fills the mold, it needs to be fully broken during the pressing process to obtain a green body with no holes inside and a densified shape. After sintering, a ceramic body with uniform density and excellent performance can be obtained. Since the hydrolysis of lithium carbonate (Li2CO3) in the LLZO / LLZMO raw materials is extremely alkaline, the pH value of the slurry prepared with pure water as a solvent can reach 13-14. During the spray granulation process, although particles with good sphericity can be obtained, the surface of the granulation powder is very easy to form a hard shell during the drying process, resulting in the granulation powder having a very high hardness. During the pressing process, it cannot be effectively broken, and the final sintered ceramic body has internal defects, which affects the service life of the material.
[0087] The present application provides a powder granulation process which can obtain powder with good sphericity and low shell hardness.
[0088] The present application proposes a method for preparing lithium-based ceramic granulated powder, which is achieved by the following method:
[0089] First, when preparing the slurry, the mass ratio of the components in the composite solvent formula is ethanol: water = 1:2-5;
[0090] In a better example, the composite solvent formula is ethanol: water = 1:3;
[0091] Compared with the method provided in the present application, when pure organic solvent (such as ethanol) is used for spray granulation, pure nitrogen (argon) is required for spray granulation of organic solvent (such as pure ethanol), and the granulated powder does not form a crust, but it is not easy to form a sphere; using pure water for granulation as mentioned above, it is very easy to form a hard shell; the invention adopts an intermediate method (ethanol + water), which ensures the sphericity after granulation and appropriately reduces the hardness of the shell, so that the particles can be effectively broken during the pressing process, and the final sintered ceramic body has fewer internal defects.
[0092] Organic solvents (such as ethanol) reduce the hydrolysis rate of the raw materials, thereby reducing the OH in the slurry. - concentration to reduce the pH of the slurry to 8-10.
[0093] In the present application, other organic solvents can also be combined with water to form a solvent, and other organic solvents include any one of propanol and n-butanol; preferably, the organic solvent is ethanol, which can be completely removed in the later stage without adding impurities to the powder.
[0094] Secondly, further, the temperature of the sprayer air inlet is reduced to 130-160°C, preferably to 145-155°C;
[0095] Compared with the prior art, the present application reduces the air inlet temperature, reduces the difference in evaporation rate of water inside and outside the granulated powder, makes the degree of shrinkage inside and outside the granulated powder as consistent as possible, and reduces the crusting phenomenon of the outer layer.
[0096] If the temperature is high, the evaporation rate of water inside and outside is uneven, the granulated powder shrinks to be higher on the outside and lower on the inside, forming excessive surface tension, resulting in the formation of an outer crust and affecting the sphericity of the particles.
[0097] Again, further, the air inlet is introduced with gas, and the gas is at least an inert gas and may also include air;
[0098] Preferably, the air inlet is passed through argon (nitrogen): air = 1:3-7;
[0099] Further preferably, the air inlet is passed through argon (nitrogen): air = 1:4.5-5.5.
[0100] In the present application, nitrogen or argon is introduced into the air inlet to reduce the oxygen content in the hot air, ensure the stable and effective volatilization of alcohol, and ensure safety to avoid ethanol explosion.
[0101] Furthermore, in the present application, since ethanol+water composite solvent is used for spray granulation, the concentration of ethanol in the composite solvent is reduced, so the air inlet can be combined with inert gas+air, which further reduces the cost while ensuring safety.
[0102] In the present application, when preparing the slurry, an organic solvent and water are used to prepare a composite solvent, which reduces the pH of the system and makes the slurry in a weakly alkaline state; and by introducing an inert gas at the air inlet, the organic solvent (such as ethanol) can be effectively, evenly and stably volatilized during the granulation process; and the temperature of the air inlet is lowered to make the evaporation rate of the water inside and outside uniform, so that the shrinkage of the granulated powder inside and outside is as consistent as possible, avoiding the formation of excessive surface tension. Combining the above means, the particles after granulation have good sphericity and the outer shell has a low hardness.
[0103] In some examples, when ethanol: water = 1:2.5-3, and the temperature is between 145 and 155°C, and argon (nitrogen): air = 1:4.5-5.5, the crushing effect is better and the density of the pressed green body is higher.
[0104] Compared with pure water as solvent and high temperature rapid drying, the hardness of the granulated powder obtained by spraying is significantly reduced after the implementation of this method. The lithium-based ceramic green body obtained by pressing the spray granulated powder through a press is observed under a scanning microscope. The fracture morphology of the two green bodies (pure water and this process) is observed. After the improved process, the granulated powder has a better crushing effect under the same pressure, and the pressed green body has a higher density. The density of the conventional green body (using the process of pure water) is 2.5-2.6g / cm 3 After improvement, the green density can reach 2.6g / cm 3 Above, further up to 2.65g / cm 3 above.
[0105] The scheme of the present application is described below in conjunction with the following specific examples. Unless otherwise specified, the raw materials used in the following examples are all from common commercial products, and the devices or equipment used are all purchased from conventional market sales channels.
[0106] How to obtain LLZTO pre-burned powder used in preparing slurry:
[0107] According to the chemical formula Li 6.4 LqCy 1.40 Ta 0.6 O 12 , prepare the raw materials, use 520.2gLi2CO3, 911.1gLa2O3, 321.6gZrO2, 247.1gTaO2; after adding water and ball milling for 5h, the slurry is dried and crushed; then pre-calcined at 1100℃ for 12h to obtain pre-calcined powder.
[0108] The pre-burned powder used in the slurry preparation process in the following embodiments is obtained by the above method;
[0109] Of course, this process does not limit the preparation method of the pre-burned powder and the chemical composition of the pre-burned powder, but only provides a possible method.
[0110] In the examples and comparative examples of the present application, the purity of ethanol is 99.5%, which is anhydrous ethanol.
[0111] Example 1
[0112] A 30wt% solid content LLZTO (LLZO doped with Ta) slurry was prepared for spray granulation (i.e., the mass ratio of the pre-sintered powder to the composite solvent was 30:70), ethanol:pure water (1:2) was used as the composite solvent, the pH value of the slurry was 8, the air inlet temperature was 130°C, and the air:argon ratio was 1:3 as the heat transfer medium. The obtained granulated powder was pressed into a lithium-based ceramic green body at a pressure of 200MPa, and the density of the lithium-based ceramic green body was 2.66g / cm 3 .
[0113] The fracture morphologies of the granulated powder and green body were observed under a scanning electron microscope. The granulated powder was round particles. From the fracture of the green body, it can be seen that some granulated powders failed to break, indicating that the hardness of the shell was relatively low.
[0114] Example 2
[0115] A 30wt% solid content LLZTO slurry was prepared for spray granulation. Ethanol: pure water (1:5) was used as a composite solvent. The pH value of the prepared slurry was 10, the air inlet temperature was 158°C, and the air: argon ratio was 1:7 as the heat transfer medium. The obtained granulated powder was pressed into a lithium-based ceramic green body at a pressure of 200MPa. The density of the lithium-based ceramic green body was 2.68g / cm 3 .
[0116] The fracture morphologies of the granulated powder and green body were observed under a scanning electron microscope. The granulated powder was round particles. From the fracture of the green body, it can be seen that some granulated powders failed to break, indicating that the hardness of the shell was relatively low.
[0117] Example 3
[0118] A 30wt% solid content LLZTO slurry was prepared for spray granulation. Ethanol: pure water (1:3) was used as a composite solvent. The pH value of the prepared slurry was 9, the air inlet temperature was 145°C, and the air: argon ratio was 1:4.5 as the heat transfer medium. The obtained granulated powder was pressed into a lithium-based ceramic green body at a pressure of 200MPa. The density of the lithium-based ceramic green body was 2.73g / cm 3 .
[0119] The fracture morphologies of the granulated powder and green body were observed under a scanning electron microscope. Figure 1 and Figure 2 As shown, from Figure 1 It can be seen that the sphericity of the spray granulated powder is very high; Figure 2 It can be seen that only a few granulated powders failed to break, indicating that the hardness of the shell was very low.
[0120] Example 4
[0121] A 30wt% solid content LLZTO slurry was prepared for spray granulation. Ethanol: pure water (1:2.5) was used as a composite solvent. The pH value of the prepared slurry was 8, the air inlet temperature was 155°C, and the air: argon ratio was 1:5.5 as the heat transfer medium. The obtained granulated powder was pressed into a lithium-based ceramic green body at a pressure of 200MPa. The density of the lithium-based ceramic green body was 2.8g / cm 3 .
[0122] The fracture morphologies of the granulated powder and green body were observed under a scanning electron microscope. The spray granulated powder obtained was similar to that in Example 3, and the sphericity was also very high. The fracture morphology of the green body was also similar to that in Example 3, and only a few granulated powders failed to break, indicating that the hardness of the shell was very low.
[0123] Comparative Example 1
[0124] A 30wt% solid content LLZTO slurry was prepared for spray granulation. Pure water was used as the solvent. The pH value of the slurry was 13. The air inlet temperature was 175°C. Air was used as the heat transfer medium. The obtained granulated powder was pressed into a lithium-based ceramic green body at a pressure of 220MPa. The density of the lithium-based ceramic green body was 2.58g / cm 3 .
[0125] The fracture morphologies of the granulated powder and green body were observed under a scanning electron microscope. Figure 3 and Figure 4 As shown, from Figure 3 It can be seen that the sphericity of the granulated powder is good, but from Figure 4 It can be seen that the granulated powder in the green body is elliptical under pressure and is not broken. There are obvious boundaries between the granulated powders, which shows that the shell has high hardness, is not easy to break, and has poor filling properties.
[0126] Comparative Example 2
[0127] A 30wt% solid content LLZTO slurry was prepared for spray granulation. Pure ethanol was used as solvent. The pH value of the slurry was 8, the air inlet temperature was 115°C, and argon was used as the heat transfer medium. The obtained granulated powder was pressed into a lithium-based ceramic green body at a pressure of 200MPa. The density of the lithium-based ceramic green body was 2.55g / cm 3 .
[0128] The fracture morphologies of the granulated powder and green body were observed under a scanning electron microscope. Figure 5 and Figure 6 As shown, from Figure 5 It can be seen that the granulated powder is not spherical, which seriously affects its fluidity. Figure 6 It can be seen that the granulated powder in the green body is basically completely crushed, and no obvious boundary marks are observed on the fracture surface of the green body.
[0129] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing lithium-based ceramic granulated powder, characterized in that: The following steps are involved: Step S1: providing raw materials according to the stoichiometric ratio of lithium-based ceramics, and pre-sintering to obtain lithium-based ceramic pre-sintered powder, wherein the raw materials include a lithium source; Step S2: mixing the lithium-based ceramic pre-sintered powder with a composite solvent to prepare a slurry, wherein the composite solvent includes an organic solvent and water; Step S3: subjecting the slurry to a spray granulation process to obtain lithium-based ceramic granulated powder.
2. The method according to claim 1, characterized in that In step S2, the organic solvent includes at least one of ethanol, propanol, and n-butanol; Preferably, the organic solvent is ethanol.
3. The method according to claim 1 or 2, characterized in that: In the step S2, in the composite solvent, the mass ratio of the organic solvent to water is 1:2-5; Preferably, the mass ratio of the organic solvent to water is 1:2.5-3.
4. The method according to claim 1, characterized in that: In the step S2, the solid content of the slurry is 20wt% to 70wt%.
5. The method according to claim 1, characterized in that In the step S2, the pH of the slurry is 8-10.
6. The method according to claim 1, characterized in that In step S3, the conditions of the spray granulation treatment include: the air inlet temperature is 130-160°C; Preferably, the air inlet temperature is 145-155°C.
7. The method according to claim 1 or 5, characterized in that: In the step S3, the conditions of the spray granulation treatment include: introducing a gas into the air inlet, wherein the gas includes an inert gas; Preferably, the gas also includes air; Preferably, the volume ratio of the inert gas to air is 1:3-7; Further preferably, the volume ratio of the inert gas to air is 1:4.5-5.
5.
8. The method according to claim 1, characterized in that The lithium-based ceramic is selected from any one of the substances shown in Formula 1; Li 7-x La3Zr 2-x M x O 12 Formula 1 Wherein, M is a doping element, and M is selected from at least one of Ta, Nb, W, and Ti; The value range of x is: 0≤x≤1.0; The lithium source includes at least one of lithium carbonate, lithium nitrate and lithium hydroxide.
9. A lithium-based ceramic granulated powder, characterized in that: Prepared according to the method according to any one of claims 1 to 8.
10. A lithium-based ceramic material, characterized in that: The lithium-based ceramic granulated powder according to claim 9 is obtained by molding and sintering; Preferably, the molding comprises: pressing the lithium-based ceramic granulated powder under a pressure of 180-220 MPa to obtain a lithium-based ceramic green body, wherein the density of the lithium-based ceramic green body is 2.6-2.80 g / cm 3 .
Citation Information
Patent Citations
Method for preparing rare earth doped yttrium aluminum garnet transparent ceramics by utilizing spray granulation modified powder
CN102060519A
Spherical lithium-containing oxide electrolyte powder material and preparation method thereof
CN113889660A
Preparation method of large-size lithium lanthanum zirconium tantalum oxide solid electrolyte
CN118754660A
Lithium-garnet solid electrolyte composite, tape articles, and methods thereof
US20180301754A1